Interventions for Preventing Cardiotoxicity in Breast Cancer Patients Receiving Trastuzumab: A Systemic Review and Bayesian Network Meta-Analysis - Li, Xinyi; Wu, Ziyang; Du, Xin; Wu, Yibo; Xie, Xiaohui; Shi, Luwen (Frontiers in Pharmacology, 2021)
Background: Trastuzumab is associated with the risk of cardiotoxicity. Here, we aim to explore interventions for preventing trastuzumab-related cardiotoxic effects in breast cancer patients. Methods: A systematic review was performed including trials of breast cancer patients with intervention to prevent cardiotoxicity of trastuzumab. Trials were searched through databases including PubMed, Embase, and Cochrane Library. Results: Eight RCTs were included. Five trials reported the outcomes of short-duration interventions, including 6-month and 9-week durations, and only 9-week treatment has a significant difference from the 12-month group (OR 0.38; 95% CI 0.18–0.83) using cardiotoxicity as the outcome. However, 6-month treatment turned out to yield less occurrence of trastuzumab discontinuation (OR 0.32; 95% CI 0.24–0.42). Three trials reported interventions of cardioprotective drugs, and there is no significant difference shown in any cardioprotective group compared with placebo (cardiotoxicity outcome: angiotensin-converting enzyme inhibitor: OR 0.48; 95% CI 0.057–2.3; angiotensin receptor blocker: OR 1.3; 95% CI 0.12–14; β-blocker: OR 0.48; 95% CI 0.057–2.3; trastuzumab interruption outcome: angiotensin-converting enzyme inhibitor: OR 0.45; 95% CI 0.12–1.3; angiotensin receptor blocker: OR 0.87; 95% CI 0.15–4.8; β-blocker: OR 0.41; 95% CI 0.11–1.2). Conclusion: Only the 9-week group has a significant difference from the 12-month group using cardiotoxicity as the outcome. And 6-month treatment turned out to yield less occurrence of trastuzumab discontinuation. The use of cardioprotective drugs failed to prevent trastuzumab-related cardiotoxic effects in breast cancer patients.